2022
DOI: 10.3389/fcimb.2022.775236
|View full text |Cite
|
Sign up to set email alerts
|

Raman Spectroscopy: A Potential Diagnostic Tool for Oral Diseases

Abstract: Oral diseases impose a major health burden worldwide and have a profound effect on general health. Dental caries, periodontal diseases, and oral cancers are the most common oral health conditions. Their occurrence and development are related to oral microbes, and effective measures for their prevention and the promotion of oral health are urgently needed. Raman spectroscopy detects molecular vibration information by collecting inelastic scattering light, allowing a “fingerprint” of a sample to be acquired. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 115 publications
(184 reference statements)
1
15
0
Order By: Relevance
“…Other studies have attempted to characterize periodontal tissues through unilateral modalities. [22][23][24] Chifor et al concluded that periodontal ultrasonography can accurately visualize the dentino-enamel junction, cortical bone, and gingival tissues to diagnose periodontal status. 25 Similarly, Tattan et al reports that ultrasonic imaging can provide accurate periodontal diagnosis without concerns about ionizing radiation when compared with clinical and CBCT readings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have attempted to characterize periodontal tissues through unilateral modalities. [22][23][24] Chifor et al concluded that periodontal ultrasonography can accurately visualize the dentino-enamel junction, cortical bone, and gingival tissues to diagnose periodontal status. 25 Similarly, Tattan et al reports that ultrasonic imaging can provide accurate periodontal diagnosis without concerns about ionizing radiation when compared with clinical and CBCT readings.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of the authors’ knowledge, this is the first study to combine RMS and μOCT into a single optical device for measurement of periodontal activity status. Other studies have attempted to characterize periodontal tissues through unilateral modalities 22–24 . Chifor et al.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the screening techniques applied in clinics sometimes suffer a lack of selectivity with respect to the separation of the intact and infected tissues, as sensitivity and reliability are needed for convenient and routine instruments for the practical diagnostics of the dental status of teeth under external inspection [ 30 , 33 ]. In our opinion, the optimal approach is to apply the diagnostic approaches based on the analysis of information about light-scattering (the use of Raman spectroscopy in vivo, as a diagnostic aid for discovering incipient caries [ 70 , 71 , 72 ]) and autofluorescent properties of the intact and affected dental tissue. Al-Obaidi et al [ 52 ] have shown that comparing the data from the fluorescence spectra (shift of the signal to the red spectral range) and confocal Raman microscopy (determination of the value for the ratio of the Raman signal for the mineral phosphate band 𝜈 2 at ~430 cm −1 and the organic matrix at ~2931 cm −1 ) enabled understanding of the changes in the chemical composition of the enamel and the separation of the demineralised and intact parts of the enamel on the surface of tooth enamel.…”
Section: Discussionmentioning
confidence: 99%
“…Raman spectroscopy (RS) is an optical spectroscopic technique using different frequencies of scattering light to characterize biological specimens ( 14 , 15 ). It probes the vibrational modes related to chemical bonds in a sample and obtains the “Raman Spectrum”, which is a unique spectral fingerprint of the sample ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…Different samples possess their chemical compositions, which give RS the ability to reveal changes in the components and structure of target samples in a non-destructive manner ( 18 ). It provides deep insights into biological activities, offering a new angle to analyze diseases and assisting in diagnosis, treatment, and prognostic evaluation ( 15 , 19 ). In fact, vibrational spectroscopy has been quite active over the past two decades.…”
Section: Introductionmentioning
confidence: 99%